(untitled) (Zoo Botanica, 2025)
The aim of the study was to understand the relationships among yield-related characteristics in eight different tomato genotypes. This research analyzed the correlations between these traits across the selected genotypes. Analysis of variance showed significant variations among all traits examined. Branches per plant was positively correlated to plant height, clusters per plant, flowers per cluster, fruit length, fruits per cluster, fruit setting percentage, fruit weight, and overall fruit yield per plant. Height of plants has shown positive relationship with clusters per plant, fruit length, fruit weight, fruits per cluster, fruits per plant and yield per plant. Clusters per plant has positive association with flowers per cluster, fruits per cluster, fruit length, fruit weight, and yield per plant. Additionally, flowers per cluster were positively correlated with fruit length. Fruits per cluster demonstrated positive correlation with fruits per plant, fruit length, fruit weight, and fruit yield per plant. Fruits per plant also exhibited a positive correlation with fruit setting percentage, fruit weight, and total yield per plant. Furthermore, fruit length was positively linked to fruit weight and yield per plant. Lastly, the fruit setting percentage showed a positive association with both fruit weight and fruit yield, while fruit weight had a strong positive association to yield per plant.